Respostas
respondido por:
2
Resposta:
Explicação passo-a-passo:
( V36 + 4³ : 14 + [ 80 : 2^4 + 6 : 3 ] =
resolvendo raiz e expoentes
V36 = V(2² * 3² )= 2 * 3 = 6 ****
4³ = 4 * 4 * 4 = 64 ***
2^4 = 2 * 2 * 2 *2 = 16
reescrevendo
( 6 + 64 ) : 14 + [ 80 : 16 + 6: 3 ] =
resolvendo primeiro parenteses
70 : 14 + [ 80 : 16 + 6 : 3 ]
fazendo as divisões
5 + [ 5 + 2 ] =
5 + 7 = 12 ***** resposta
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás